Comparison of laparoscopic‐assisted technique and open laparotomy for gastrointestinal biopsy in cats*. Issue 6 (8th May 2017) - McClaran, Janet Kovak; Skerrett, Suzanne C.; Currao, Rachael L.; Pavia, Philippa R.; Tarvin, Kiki M.
Abstract: Objective: To evaluate and compare the complications, postoperative pain, surgical time, hospitalization time, and adequacy of biopsy specimens between laparoscopic assisted (LAP) versus open laparotomy (OPEN) gastrointestinal biopsies in cats. Study Design: Prospective randomized clinical study. Sample Population: Twenty‐eight cats with clinical and ultrasonographic evidence of gastrointestinal disease. Fifteen cats in the LAP group and 13 in the OPEN group. Methods: Signalment, presenting clinical signs, total duration of surgery, operative time, ease of procedure, incision length, postoperative pain scores, complications, and duration of hospitalization were recorded. Quality of gastrointestinal biopsies was compared between techniques. Results: There was no difference in frequency of intraoperative complications ( P = .778), surgical duration ( P = .333), postoperative complications ( P = .722), or duration of hospitalization ( P = .728). Pain scores assigned before ( P = .198) or 1 hour after surgery ( P = .073) did not differ between groups; however, pain scores were lower at 6 hours ( P = .003), 12 hours ( P = .001), and 24 hours ( P = .005) postoperatively in the LAP group. All cases survived surgery, with one case requiring conversion, and diagnostic biopsies were obtained in all cases. Conclusion: Laparoscopic‐assisted gastrointestinal biopsy technique provided diagnostic specimens and decreased postoperative pain compared to open surgical techniques. No difference was detected in surgical duration, complications, or duration of hospitalization.